COMPARISON OF THE EFFICACY OF HONEY DRESSING VERSUS OXO FERRIN DRESSING IN THE MANAGEMENT OF INFECTED DIABETIC FOOT ULCERS (The Research of Medical Science Review, 2025)
Background: Infected diabetic foot ulcers (DFUs) are a common complication of diabetes, often leading to severe morbidity and mortality. Effective wound management is crucial to improve healing outcomes and reduce complications. This study compared the efficacy of honey dressing and Oxoferin dressing in managing infected DFUs, focusing on wound healing rates, microbial load reduction, and patient-reported outcomes. Methods: A randomized controlled trial design was employed, involving 100 participants with type 2 diabetes, aged 30–70 years, presenting with Wagner grade 1 or 2 infected DFUs. Participants were randomly assigned to receive either honey dressing or Oxoferin dressing, alongside standard wound care procedures, over an eight-week period or until complete healing. Outcomes assessed included wound size reduction, time to complete healing, microbial load reduction, pain reduction (measured using the Visual Analog Scale), infection clearance, and patient satisfaction. Statistical analyses were conducted using independent t-tests, chi-square tests, Kaplan-Meier analysis, and Cox regression. Results: Baseline demographic and clinical characteristics were comparable between groups. Honey dressing showed a wound size reduction in 22.4% of patients compared to 49% in the Oxoferin group (p < 0.05). The mean time to complete wound healing was significantly shorter in the Oxoferin group (5.2 weeks) compared to the honey group (8.5 weeks; p < 0.01). Microbial load reduction was higher in the Oxoferin group (75%) than in the honey group (45%; p < 0.01). Pain reduction was also more pronounced with Oxoferin (mean VAS score reduction of 6.0) than honey (3.5; p < 0.05). Infection clearance rates were 90% in the Oxoferin group compared to 60% in the honey group (p < 0.01). Patient satisfaction was higher with Oxoferin dressing (92%) than honey dressing (75%; p < 0.05). Conclusion: Oxoferin dressing demonstrated superior efficacy compared to honey dressing in managing infected DFUs, with faster wound healing, greater microbial load reduction, more significant pain relief, higher infection clearance rates, and greater patient satisfaction. These findings suggest that Oxoferin dressing may be a more effective option for treating infected DFUs in clinical settings.